The Effectiveness of Fluroxypyr Meptyl and Ammonium Glufosinate Herbicides in Controlling Weeds in The Field Oil Palm (Elaeis quineensis Jacq.) - Girsang, Warlinson; Girsang, Rosmaria; Zamriyetti, Zamriyetti; Renizuida, Renizuida; Hutagalung, Yehezkiel (Jurnal Penelitian Pendidikan IPA, 2023)
In oil palm plantations, weed control using herbicides is considered more practical than other control methods. This is due to the need for less manpower, shorter control execution times and longer control cycles. The ability of herbicides to control weeds is determined by the type of active ingredients they contain. The aim of the study was to determine the effectiveness of the 2 types of herbicides and the appropriate dosage levels to control weeds in oil palm fields. The research method used a nested design, testing 2 types of herbicides namely fluroxypyr-mepthyl and ammonium glufosinate. While the second treatment, tested the dose level of each herbicide. The tested dose levels for the herbicide fluroxypir-mepthyl were 0.1 l/ha, 0.3 l/ha, 0.5 l/ha, 0.7 l/ha and 0.9 l/ha. While the dose levels of ammonium glufosinate herbicide were 2.6 l/ha, 2.8 l/ha, 3.0 l/ha, 3.2 l/ha and 3.4 l/ha respectively. The results showed that the effectiveness of the herbicides fluroxypir meptyl and ammonium glufosinate to control weeds in oil palm plantations was not significantly different. The most effective dosage level of the herbicide fluroxypir meptyl for controlling weeds was 0.9 l/ha (average percentage of weed mortality was 74%). The dosage level of the ammonium glufosinate herbicide which resulted in the highest percentage of weed death (74.44%) resulted in an application dose of 3.4 l/ha. Application of the herbicides fluroxypir meptyl and ammonium glufosinate at all dose levels tested did not show toxicity in oil palm plants.